Promovendo a Compreensão de Regras em Processos de Prestação de serviços Públicos Utilizando a Animação - Gomes, Jorge Moreira; Araujo, Renata (Anais do Latin American Symposium on Digital Government (LASDiGov), 2012)
The high degree of access to information has given rise to a society in which citizens expect greater clarity and effectiveness from public services. Electronic Government initiatives are promoting a new form of interaction between citizens and public administration. Its adoption considers factors such as transparency of organizational processes, represented by models consisting of activities, flows, actors and business rules that determine how a service runs. In this paper we present a proposal for increasing the understanding of the citizen in relation to how a public service runs, based on the use of an animation process to facilitate the communication between the parties involved in solving a problem.